The Number of Sample Trees Required for Determining Volumes of Woods with Various Degrees of Accuracy - Dwey, Reginald (Indian Forester, 1943)
Little attention has been paid to the numbers of sample trees required for a given standard of accuracy. In order to investigate the question 422 trees from 16 plantations in the south of England were measured on the ground. These enabled the determination of the probable scatter of taper height. The resulting statistics, combined with assumed errors of measurement of standing trees, provided an indication of the general magnitude of the maximum standard. Deviations likely to be found in practice. The numbers of sample trees required for a 21 to 1 chance of a total volume within 6 per cent. And 8 per cent. Of the true volume were determined for hardwoods and conifers.